2009
DOI: 10.1007/s00339-009-5359-z
|View full text |Cite
|
Sign up to set email alerts
|

Engineering a material for biomedical applications with electric field assisted processing

Abstract: In this work, using multiple co-flows we demonstrate in-situ encapsulation of nano-particles, liquids and/or gases in different structural morphologies, which can also be deposited in a designated pattern by a direct write method and surface modification can be controlled to release encapsulated material. The range of possibilities offered by exposing a material solution to an applied electric field can result in a plethora of structures which can accommodate a whole host of biomedical applications from microf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…Buchko et al fabricated microarray using electrospray deposition with a conductive mask where deposition occurs on both mask and substrate evenly, resulting in the loss of raw materials and poor spot density due to lack of focusing effect. [20][21][22][23] Although Morozov et al used a dielectric mask for electrospray deposition, the deposition efficiency was improved comparing to the method by Buchko et al, the interspot distance was still large (1 mm) and it was limited to the dielectric mask and conductive substrate. 24,25 Kim et al used a dielectric mask and a conductive substrate with a combination of a surface acoustic wave atomizer and electrostatic deposition to fabricate protein chips.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Buchko et al fabricated microarray using electrospray deposition with a conductive mask where deposition occurs on both mask and substrate evenly, resulting in the loss of raw materials and poor spot density due to lack of focusing effect. [20][21][22][23] Although Morozov et al used a dielectric mask for electrospray deposition, the deposition efficiency was improved comparing to the method by Buchko et al, the interspot distance was still large (1 mm) and it was limited to the dielectric mask and conductive substrate. 24,25 Kim et al used a dielectric mask and a conductive substrate with a combination of a surface acoustic wave atomizer and electrostatic deposition to fabricate protein chips.…”
Section: Introductionmentioning
confidence: 91%
“…38,39 Most recently, Li et al and Ahmad et al examined inorganic hydroxylapatite nanocrystal pattern formation using template-assisted electrohydrodynamic atomization spraying and their potential biomedical applications. [21][22][23] In contrast, electrospray deposition has not yet been commonly used to fabricate polymeric particle pattern. In our previous studies, controllable size and morphology of biodegradable polymeric particles were achieved by electrospray approach.…”
Section: Introductionmentioning
confidence: 91%
“…Favourable physical characteristics of low density combined with high surface area make polymeric nanospheres an ideal drug carrier system (Wang et al, 2007). There are several techniques including emulsion polymerization, solvent evaporation and electrohydrodynamic atomization to prepare nanospheres (Ahmad et al, 2009a;Gunduz et al, 2013;Saito et al, 2006). The flow focusing methods such as T-junction and V-junction microfluidic (VJM) devices have also gained considerable attention (De Koker et al, 2012;Serra and Chang, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…These particles were nearly spherical with a diameter of 3 mm and have interconnected porosity with diameters close to 1.3 mm. Ahmad et al (2009) also reported the formation of ceramic bubbles from preceramic polymers via electrospraying.…”
Section: Introductionmentioning
confidence: 99%